The Effect of Online Learning on Academic Stress on Students - Eric Arizona Samudra; Andik Matulessy (Journal Research of Social Science, Economics, and Management, 2021)
The policies carried out by the Indonesian government to reduce the number of COVID-19 cases include implementing health protocols, namely maintaining a distance so that theteaching and learning process in schools and campuses in each university uses the distancemethod as an effort to prevent the development and spread of COVID-19. Rapid and suddenchanges in the education system can cause intense academic stress on students. The purpose of this study was to determine whether online learning can affect academic pressure on students. The subjects of this study were undergraduate students from several universities, both PTN and PTS spread across Java Island, who participated in online learning as many as 237 students or participants who had filled out the online learning scale and the Educational stress scale for adolescents (ESSA). This test uses SLR (Simple Linear Regression) SPSS 20.0 for windows with the results of a simple linear regression test between online learning and academic stress, the calculated F value = 5.110 at a significance level of p = 0.027 (p < 0.01). The results show asignificant relationship between distance learning independent variable (X) and learning stressdependent variable (Y). So it can be concluded that there is an important relationship between online learning and academic stress. The implications of the results of this study are expected to be a reference for related parties to evaluate the online learning system so that it does not have an impact on increasing academic stress on students.